Community Service Monitoring Information System at The Level of Community Harmony of Citizens - Romario Firera; Akbar Iskandar (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
A website-based community service information system can improve the performance of sub-district, village, community units and neighborhood units so that it can speed up report generation and can also improve the quality of better services because it is faster and without queuing. This research is to design and build an Information System for the Rukun Warga (RW) Service at Perumnas Antang Blok 10 by using the System Development Life Cycle (SDLC) method and the Multi-Objective Optimization On the Basis Of Ratio Analysis (MOORA) method that is able to provide effective services. and efficient to citizens and able to facilitate in supporting decision making acceptance of social assistance. The results of the study show that the Community Service Information System (RW) at Perumnas Antang Blok 10 can help provide effective and efficient services to residents and is able to facilitate decision making in receiving social assistance. Based on the results of the respondent's assessment through the distribution of questionnaires, the Information System for the Rukun Warga (RW) at Perumnas Antang Blok 10 is very good to use because it meets the final score criteria of 88%.